2021
DOI: 10.3390/molecules26030682
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Butyrate against Obesity and Obesity-Related Diseases

Abstract: Worldwide obesity is a public health concern that has reached pandemic levels. Obesity is the major predisposing factor to comorbidities, including type 2 diabetes, cardiovascular diseases, dyslipidemia, and non-alcoholic fatty liver disease. The common forms of obesity are multifactorial and derive from a complex interplay of environmental changes and the individual genetic predisposition. Increasing evidence suggest a pivotal role played by alterations of gut microbiota (GM) that could represent the causativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(109 citation statements)
references
References 166 publications
4
102
0
3
Order By: Relevance
“…It has been reported that the abundance of Bacteroidales family S24-7 was high in CD obesity-prone rats fed resistant starch [40]. A resistant starch diet has been reported to increase butyrate production by intestinal microbiota [41]. The relationship between butyric acid and Bacteroidales family S24-7 requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the abundance of Bacteroidales family S24-7 was high in CD obesity-prone rats fed resistant starch [40]. A resistant starch diet has been reported to increase butyrate production by intestinal microbiota [41]. The relationship between butyric acid and Bacteroidales family S24-7 requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…One of the greatest challenges in defining “a healthy gut” is that most of the variance (~85%) within the human microbiome is still unaccounted for, as confirmed by population-wide studies [ 76 , 77 ]. However, the relative abundance of microbes able to ferment non-digestible substrates such as dietary fibres to produce short-chain fatty acid (SCFAs) continues to be one of the indisputable criteria for such a definition [ 78 , 79 , 80 , 81 , 82 ]. Of the major SCFAs produced—acetate, propionate and butyrate—butyrate is particularly important for the simple reason that it constitutes the main energy source for colonocytes [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that butyric acid is able to interact with the orexigenic neurons present in the hypothalamus, whose role is to mediate food intake and provide a protective effect against the effects of a high-fat diet [ 90 ]. Furthermore, a lower presence of butyrate-producing bacteria has been linked with an increased risk of metabolic disease [ 91 ]. A study was conducted with obese volunteers suffering from metabolic syndrome, who were administered with sodium butyrate (4 g/day), showing a positive anti-inflammatory and immunomodulatory effect [ 92 ].…”
Section: Discussionmentioning
confidence: 99%